INVESTIGATING THE EFFECT OF FREEWRITING TECHNIQUES ON THE WRITING SKILLS OF INDONESIAN JUNIOR HIGH SCHOOL STUDENTS - Ummu Atiah; Akhmad Baihaqi; Dhafid Wahyu Utomo (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
The aim of this study was to investigate the effects of using the freewriting techniques on the writing ability of Indonesian junior high school students in producing descriptive texts. The study was conducted in a private school located in Banten province and involved 33 students who were selected through a total sampling. A quasi-experimental design was used, with pre- and post-tests serving as the research instruments. The tests were validated for content validity and inter-rater reliability. The results were analyzed using a t-test, which showed that the use of freewriting techniques had a significant positive effect on the writing ability of the students. The t-count (2.533) was higher than the t-table (2.039) at a significance level of 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. The average score of the experimental class was higher than that of the control class, further emphasizing the positive impact of the freewriting techniques. These results suggest that the implementation of freewriting as a teaching techniques has the potential to enhance the writing ability of Indonesian junior high school students.